Natural infection of the feline lungworm Aelurostrongylus abstrusus in the invasive snail Achatina fulica from Argentina - Valente, Romina (2017)
The giant African snail Achatina fulica is an invasive mollusk native to Africa, the first record in Argentina was in Puerto Iguazú, in northeastern Argentina in 2010. Recently it was reported in Corrientes Province. This snail can act as an intermediate host of Metastrongyloidea nematodes of importance in public health as: Angiostrongylus cantonensis, Angiostrongylus costaricensis and Angiostrongylus vasorum. Taking into account the presence of A. fulica in Argentina, the objectives of this study is to assess the presence of Metastrongyloidea nematodes in this mollusk species in Puerto Iguazú, Misiones, close to the international border with Brazil and Paraguay. A total of 451 samples were collected from February 2014 to November 2015. The snails were processed using a digestion technique to recover the parasites. A total of 206 nematodes larvae were founded in the digestion solution of 10 hosts (P = 2%; MA = 0.5; MI = 21). Third larval stage (L3) nematodes identified as Aelurostrongylus abstrusus were founded parasitizing the snails. No other larval stage was observed. This species has veterinary importance because it causes ‘aelurostrongilosis’, also known as feline strongyloidosis. This study constitutes the first record of a Metastrongyloidea nematode in A. fulica in Argentina and also highlights the susceptibility of this mollusk as intermediate host of other helminthes of health importance. The present study suggests that there is a need to establish an epidemiological monitoring system in order to prevent the possible installation of an infected mollusks focus.